QTL Analysis of Five Silique-Related Traits in Brassica napus L. Across Multiple Environments - Zhao, Xiaozhen; Yu, Kunjiang; Pang, Chengke; Wu, Xu; Shi, Rui; Sun, Chengming; Zhang, Wei; Chen, Feng; Zhang, Jiefu; Wang, Xiaodong (Frontiers in Plant Science, 2021)
As an important physiological and reproductive organ, the silique is a determining factor of seed yield and a breeding target trait in rapeseed (Brassica napus L.). Genetic studies of silique-related traits are helpful for rapeseed marker-assisted high-yield breeding. In this study, a recombinant inbred population containing 189 lines was used to perform a quantitative trait loci (QTLs) analysis for five silique-related traits in seven different environments. As a result, 120 consensus QTLs related to five silique-related traits were identified, including 23 for silique length, 25 for silique breadth, 29 for silique thickness, 22 for seed number per silique and 21 for silique volume, which covered all the chromosomes, except C5. Among them, 13 consensus QTLs, one, five, two, four and one for silique length, silique breadth, silique thickness, seed number per silique and silique volume, respectively, were repeatedly detected in multiple environments and explained 4.38%–13.0% of the phenotypic variation. On the basis of the functional annotations of Arabidopsis homologous genes and previously reported silique-related genes, 12 potential candidate genes underlying these 13 QTLs were screened and found to be stable in multiple environments by analyzing the re-sequencing results of the two parental lines. These findings provide new insights into the gene networks affecting silique-related traits at the QTL level in rapeseed.